THE PROBLEM FACED BY STUDENTS OF ISLAMIC EDUCATION IN READING ISLAMIC COMPREHENSION TEXT - Nyayu Yayu Suryani (University of Kuningan, 2022)
Students are often concerned with accuracy in pronouncing words when reading and not entirely focused on the content of what is being read. This study aims to find out the problems faced in reading comprehension (Islamic reading text) by employing descriptive quantitative approaches. The method used in this study was the descriptive quantitative which translates data into numbers.The sample was 59 students of the Islamic Education study program Raden Fatah Islamic State University Palembang. Furthermore, the data were gathered by using test and questionnaire as the instrument via Google form. The result showed that most students failed reading comprehension assessments due to a lack of vocabulary, poor grammatical proficiency, difficulty in understanding long phrases and material, lack of media learning or family assistance, and lack of information about reading comprehension. In conclusion, the data obtained from the test showed that the Islamic students still have difficulties in reading comprehension tests.